147k views
5 votes
How do I solve this equation? It says solve for x in the equation above

How do I solve this equation? It says solve for x in the equation above-example-1

1 Answer

3 votes

Answer:

x = -6/5

Explanation:

Note that 2 log-to-the-base-2 of 3 is equivalent to log-to-the-base-2 of 3^2, or log-to-the-base-2 of 9.

Also: log-to-the-base-2 of 9 + log-to-the-base-2 of (x + 1) is equivalent to

log-to-the-base-2 of 9(x + 1), and thus we have:

log-to-the-base-2 of 9(x + 1) = log-to-the-base-2 of (4x + 3)

And so:

log-to-the-base-2 of 9(x + 1) log-to-the-base-2 of (4x + 3)

2 = 2

Because this is true, we can conclude that 9(x + 1) = (4x + 3).

Combining like terms results in 5x + 9 = 3, or 5x = -6. Then x = -6/5

User Frank R
by
4.9k points